Trabecular bone score and sclerostin concentrations in patients with primary adrenal insufficiency - Zdrojowy-Wełna, Aleksandra; Halupczok-Żyła, Jowita; Słoka, Natalia; Syrycka, Joanna; Gojny, Łukasz; Bolanowski, Marek (Frontiers in Endocrinology, 2022)
Background: Patients with primary adrenal insufficiency need lifelong replacement therapy with glucocorticoids and mineralocorticoids, which may influence their bone quality. Aim: The aim of the study was to evaluate densitometry parameters, trabecular bone score and sclerostin concentrations in patients with primary adrenal insufficiency in comparison to control group. Materials and methods: We included 29 patients (62% females) with diagnose of autoimmune primary adrenal insufficiency (mean age 49.7 ±11.7 years, mean duration of the disease 13.2± 13.6 years) and 33 healthy subjects (adjusted with age, sex and body mass index). Bone mineral density at the femoral neck, lumbar spine, total body and trabecular bone score were evaluated. Serum sclerostin concentrations were measured. Results: There were no significant differences in densitometry parameters (T-score, Z-score, bone mineral density in all locations) as well as in trabecular bone score in patients with adrenal insufficiency in comparison to control group. Mean serum sclerostin concentration was significantly higher in patients with adrenal insufficiency than in control group (44.7±23.5 vs 30.7±10.4 pmol/l, p=0.006). There was a negative correlation between trabecular bone score and the duration of adrenal insufficiency and age, also a negative correlation between femoral neck and total densitometry parameters and 24-hour urine cortisol as a marker of hydrocortisone daily dose in patients with adrenal insufficiency. Conclusions: The bone status in patients with primary adrenal insufficiency was not impaired in comparison to control group, while sclerostin concentration was higher. The duration of the disease and higher hydrocortisone doses may affect negatively bone status.